Rejuvenating ecosystem services through reclaiming degraded land for sustainable societal development: Implications for conservation and human wellbeing. (January 2022) - Rawat, Lakhpat Singh; Maikhuri, Rakesh Kumar; Bahuguna, Yateesh Mohan; Jugran, Arun Kumar; Maletha, Ajay; Jha, Nabi Kanta; Phondani, Prakash Chandra; Dhyani, Deepak; Pharswan, Dalbeer Singh; Chamoli, Sudhanshu
Abstract: The Himalayan ecosystem has global significance for supporting unique and rich ecological and socio-cultural diversity as well as a range of ecosystem services important for the very survival of human beings. However, constant anthropogenic pressure, unsustainable developmental practices and climate change led to the transformation of irrational land-use practices that have seriously compromised the ecosystem productivity and livelihood of the mountain communities. Considering the above, integrated land use planning, effective land use policy and legislation is a key element to address unsustainable land-use practices in the Himalayan ecosystem. Realising the increasing trend of degradation of natural resources and associated livelihood challenges for rural communities, a comprehensive scientific framework was developed for improving the functionality of marginal degraded land. A total of twelve tree species used for a variety of purposes prioritised by local communities based on ecological, social and economic value were selected for plantation on marginal degraded land belonging to the village community. Significant improvement in survival rate, growth, and circumference of planted tree species was observed across the sites after ten years of the plantation. The plantation activities enhanced the net productivity of degraded landscape while increasing characteristics of soil leading to increment in water percolation, improve soil moisture and decreased runoff. Total biomass accumulated by tree species planted in three selected sites within the period significantly contributed to carbon sequestration thus reducing the adverse impact of changing climate. The provisioning services in the form of fuel, fodder, and grasses obtained from developed landscapes reduced the drudgery and workload of marginal communities. The study advocates interdisciplinary knowledge production, enrich social learning among stakeholders, improved understanding of current and future challenges associated with land-use practices and relevant policy implications for sustainable land management in the region. Graphical Abstract: ga1 Highlights: Growing bioenergy plantation on degraded land rejuvenates multiple ecosystems services. We developed a wider framework for successful implementation of restoration programme. Long term ecological and economic attributes of the developed models was assessed. The tree crops planted on degraded land significantly enhanced the provision of ecosystem services. The study advocates interdisciplinary knowledge production and relevant policy implications.